Surveillant Companionship and the FBI Agent Meme - Erdener, Jasmine (Surveillance & Society, 2024)
In late 2017 and throughout 2018, surveillance discourse collided with meme culture through the popular “FBI agent” meme. The meme had various iterations but usually depicted ordinary individuals who are aware that they are constantly being surveilled on their personal devices by an assigned government agent. However, far from threatening Orwellian depictions of surveillance, in which a dangerous government is constantly watching, the FBI agent meme characterized the surveillant relationship as positive and caring, where the government agent is answering questions or helping with homework, providing a sympathetic ear for relationship troubles, crying over movies together, and even dropping by to deliver milk. The joke is predicated on the assumption that the government agent is always watching, knows the individual intimately, communicates with them regularly, and sometimes even intervenes through their devices, but only with the individual’s best interests in mind. The FBI agent meme depicts the relationship between the individual and the surveillant apparatus as one of surveillant companionship. Surveillant companionship suggests that surveillance fulfills a social role: partly care and control, and partly a response to widespread alienation. The FBI agent meme’s depiction of surveillant companionship satirizes the normalization of mass surveillance by highlighting the absurdity of sharing every intimate moment with the surveillant gaze. Memes also function as collective interventions in political discourse, in this case mass surveillance. Although the meme depicts the surveillant apparatus as a form of ambivalent companionship, the collective and collaborative nature of memes and the participation in communal humor and critique offers a different kind of companionship, one organized around a recognition of shared grievances and surveillant intrusions.